Iodine-doped sulfide electrolyte and preparation method thereof

By doping iodine elements on the surface of the sulfur-silver pleated electrolyte to form a lithium iodide interface protective layer, the problem of poor compatibility between the metal lithium negative electrode and the sulfur-silver pleated electrolyte is solved, and the circulation performance and safety of lithium-ion batteries are improved.

CN116344921BActive Publication Date: 2025-04-29YANGTZE DEITA GRADUATE SCHOOI OF BEIJING INST OF TECH (JIAXING) +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310128864.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-03
Publication Date
2025-04-29
Estimated Expiration
2043-02-03

AI Technical Summary

Technical Problem

The interface compatibility between the metal lithium negative electrode and the sulfur-silver pleated ore-type electrolyte is poor, resulting in an increase in interface impedance, a decrease in performance, and a safety hazard.

Method used

By doping iodine elements on the surface of sulfur-silver pleated electrolytes, liquid phase synthesis technology and high-temperature calcination process, a surface-doped lithium iodide interface protective layer is formed to improve the interface stability of metal lithium batteries.

Benefits of technology

The uniform deposition of lithium and the inhibition of interfacial side reactions are achieved, the cycle performance and safety of the battery are improved, and process complexity and production costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116344921B_ABST
    Figure CN116344921B_ABST
Patent Text Reader

Abstract

The present invention relates to an iodine-doped sulfide electrolyte and a preparation method thereof, belonging to the technical field of battery materials. The chemical formula of the electrolyte is Li6PS5Cl x I 1‑x , 0.5
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an iodine-doped sulfide electrolyte and a preparation method thereof, belonging to the technical field of battery materials. Background Art

[0002] New energy vehicles and other industries have achieved rapid development in recent years. In the face of the continuous improvement of people's demand level, the development of power batteries such as lithium-ion is also moving towards a safer and higher energy density. The commonly used graphite anode is difficult to meet the development needs of high-energy-density batteries, while the metal lithium anode has a high specific capacity and low redox potential, so it is an ideal negative electrode material for lithium-ion batteries. However, during use, metal lithium will react with the organic electrolyte to form an unstable solid electrolyte membrane (SEI) at the interface, causing problems such as uneven lithium deposition, lithium dendrite growth, and "dead lithium" generation, resulting in battery capacity loss and shortened cycle life. At the same time, the growth of dendrites will pierce the diaphragm to cause a short circuit, ignite the electrolyte, and cause serious safety hazards.

[0003] The use of solid electrolytes instead of flammable organic electrolytes can greatly improve the safety of batteries. At the same time, solid electrolytes play an important role in inducing uniform lithium deposition, inhibiting lithium dendrite growth and the formation of "dead lithium", which makes the application of metallic lithium anode possible. Therefore, the research and development of solid electrolyte materials is extremely important. As an important component of inorganic solid electrolytes, thiourea-type sulfide electrolytes, represented by Li6PS5Cl, have high ionic conductivity and excellent mechanical properties comparable to organic electrolytes. They can reduce the grain boundary impedance of electrolytes by cold pressing, and have attracted extensive attention from researchers. However, the interface compatibility between metallic lithium anode and thiourea-type electrolytes is poor. This is due to the high reactivity between metallic lithium and electrolytes. Sulfides are easily reduced and decomposed by metallic lithium to form an unstable interface layer. The uncontrollable growth of the interface layer will increase the interface impedance with continuous cycling, eventually leading to performance degradation.

[0004] The further development of sulfide electrolytes requires solving problems such as interfacial contact with metallic lithium negative electrodes. At present, researchers mainly use the method of constructing a protective layer between the electrolyte and metallic lithium to suppress side reactions between the interfaces. For example, in Chinese patent application CN108736069A, the inventors used atomic layer deposition technology to form a metal oxide coating at the electrolyte interface to stabilize the interfacial reaction with metallic lithium. Although such methods can be effective to a certain extent, they are limited in large-scale applications due to the complex process of introducing the protective layer. At the same time, the compatibility issues between the protective layer and the electrolyte also need to be considered. Therefore, it is necessary to develop a method for modifying the sulfide electrolyte itself to achieve efficient matching with metallic lithium, while also considering the development needs of large-scale production. Summary of the Invention

[0005] In view of this, the first object of the present invention is to provide an iodine-doped sulfide electrolyte with stable interfacial contact with a lithium metal anode. By controlling the doping of iodine elements on the surface of the sulfide electrolyte, an interfacial protective layer can be in-situ generated during the contact with lithium to improve the interfacial contact with metallic lithium and enhance the cycling performance of the battery.

[0006] The second object of the present invention is to provide a general preparation method for iodine-doped sulfide electrolytes suitable for large-scale production. By introducing iodine-element-containing precursors during the preparation process and adopting a liquid-phase synthesis technique assisted by organic solvents, the precursors can be uniformly mixed in the liquid phase, which is conducive to full reaction during subsequent high-temperature calcination. The synthesis process of this method is simple, with low input costs and strong material uniformity.

[0007] To achieve the above objects, the technical solutions of the present invention are as follows:

[0008] An iodine-doped sulfide electrolyte, the chemical formula of the electrolyte is Li6PS5Cl x I 1-x , 0.5 < x < 1; the iodine element is doped on the surface of the argyrodite-type electrolyte Li6PS5Cl.

[0009] Preferably, 0.5 < x ≤ 0.7.

[0010] A preparation method for the iodine-doped sulfide electrolyte of the present invention, the method steps include:

[0011] (1) Under an inert gas atmosphere, weigh Li2S, LiCl, P2S5, and LiI raw materials according to stoichiometric ratios, and dissolve Li2S, LiCl, and P2S5 in organic solvent A and stir to form a precursor solution;

[0012] (2) Heat and dry the precursor solution to remove organic solvent A to obtain a precursor;

[0013] (3) Place the precursor in an organic solvent B solution of LiI, heat and stir for surface doping of iodine elements to obtain a doped precursor solution;

[0014] (4) Heat and dry the doped precursor solution to remove organic solvent B to obtain a mixed precursor;

[0015] (5) Grind the mixed precursor evenly, place it in a muffle furnace, calcine it under an inert gas atmosphere, and cool down after calcination to obtain an iodine-doped sulfide electrolyte.

[0016] Preferably, in step (1), the organic solvent A is one or more of absolute ethanol, anhydrous acetonitrile, and anhydrous tetrahydrofuran.

[0017] Preferably, in step (1), the mass fraction of the precursor solution is 3 to 6 wt %.

[0018] Preferably, in step (1), the stirring time is 4 to 6 hours.

[0019] Preferably, in step (2), the heating and drying temperature is 160-180° C., and the drying time is 3-5 hours.

[0020] Preferably, in step (3), the organic solvent B is one or more of anhydrous acetonitrile, anhydrous tetrahydrofuran and anhydrous toluene.

[0021] Preferably, in step (3), the mass fraction of the organic solvent B solution of LiI is 3-6 wt %.

[0022] Preferably, in step (3), the heating and stirring temperature is 60 to 80° C., and the stirring time is 6 to 8 hours.

[0023] Preferably, in step (4), the heating and drying temperature is 160-180° C., and the drying time is 5-8 hours.

[0024] Preferably, in step (5), the grinding time is 10 to 30 minutes.

[0025] Preferably, in step (5), the calcination temperature is 450-600° C. and the calcination time is 4-6 hours.

[0026] Preferably, in step (5), during calcination, the heating rate is 1-5°C / min, and the cooling rate is 1-3 / min.

[0027] Preferably, the protective gas is nitrogen or an inert gas.

[0028] A lithium ion battery, wherein the electrolyte of the battery is the iodine-doped sulfide electrolyte described in the present invention.

[0029] Beneficial Effects

[0030] The present invention provides an iodine-doped sulfide electrolyte. Iodine is doped on the surface of a thiourea-type electrolyte. After contacting with metallic lithium, an interface protective layer rich in lithium iodide can be formed in situ at the interface during a cycle due to the enrichment of iodine on the electrolyte surface. The uniform deposition of lithium can be induced and the occurrence of interface side reactions can be inhibited, thereby improving the interface stability of the sulfide electrolyte to a metallic lithium battery, reducing the polarization voltage of a symmetrical battery, and enhancing the battery cycle stability.

[0031] The present invention provides a method for preparing an iodine-doped sulfide electrolyte. By introducing an iodine-containing precursor during the synthesis process for surface coating and doping and controlling the high-temperature sintering process, a thiourea-type electrolyte with surface iodine doping can be obtained. By adopting an organic solvent-assisted liquid-phase synthesis method, the uniformity of mixing between precursors is significantly improved, and the particle size is reduced, which is conducive to sufficient reaction between substances during the subsequent high-temperature sintering process, and also ensures that the synthesized electrolyte has a high ionic conductivity. The liquid-phase synthesis method of the present invention simplifies the synthesis process, has a simple process, low investment cost, and strong material uniformity, and is suitable for large-scale production and preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The X-ray diffraction (XRD) test patterns of the sulfide electrolytes prepared in Example 1 of the present invention and Comparative Example 1 are compared.

[0033] Figure 2 The electrochemical impedance spectroscopy (EIS) test spectra of the sulfide electrolytes prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 3 are compared.

[0034] Figure 3 The test results of the symmetrical batteries assembled with the sulfide electrolytes prepared in Example 3 of the present invention and Comparative Examples 1 and 3 are compared for the stability of metallic lithium. DETAILED DESCRIPTION

[0035] The present invention will be further described in detail below in conjunction with specific embodiments.

[0036] Example 1

[0037] (1) In a glove box under argon atmosphere, weigh Li2S, P2S5, LiCl, and LiI raw materials with a stoichiometric ratio of Li2S:P2S5:LiCl:LiI=5:1:1.8:0.2, and mix and dissolve Li2S, P2S5, and LiCl in anhydrous tetrahydrofuran, control the mass fraction of the precursor in the solution to be 4wt%, and continue stirring for 6h to form a uniform beige solution to obtain a precursor solution.

[0038] (2) placing the precursor solution on a heating table and heating it to 160° C. for 6 h in an argon atmosphere in a glove box to remove the organic solvent, thereby obtaining a dry sulfide electrolyte precursor.

[0039] (3) The dried sulfide electrolyte precursor is placed in an anhydrous tetrahydrofuran solution containing 4 wt % of LiI, and heated and stirred at 80° C. for 8 h until a uniform solution is formed, so as to achieve surface doping of iodine in the sulfide electrolyte precursor.

[0040] (4) placing the mixed solution obtained in step (3) on a heating table, and heating it to 160° C. for 6 h in an argon atmosphere in a glove box to remove the organic solvent, thereby obtaining a dry iodine-doped sulfide electrolyte precursor.

[0041] (3) The dried iodine-doped sulfide electrolyte precursor obtained in step (2) is placed in a mortar and ground by hand for 10 minutes to form a precursor powder. The powder is transferred to a muffle furnace and heated to 550°C in an argon atmosphere in a glove box at a heating rate of 2°C / min and sintered for 6 hours, and then slowly cooled to room temperature at a cooling rate of 2°C / min to obtain an iodine-doped sulfide electrolyte Li6PS5Cl 0.9 I 0.1 .

[0042] (4) In an argon atmosphere in a glove box, the electrolyte powder was placed in a tablet pressing mold with a diameter of 10 mm and pressed into a solid electrolyte sheet at 300 MPa.

[0043] Example 2

[0044] In this embodiment, the stoichiometric ratio in step (1) is: Li2S:P2S5:LiCl:LiI=5:1:1.6:0.4, and the rest is the same as in Example 1, to obtain an iodine-doped sulfide electrolyte Li6PS5Cl 0.8 I 0.2 .

[0045] Example 3

[0046] In this embodiment, the stoichiometric ratio in step (1) is: Li2S:P2S5:LiCl:LiI=5:1:1.4:0.6, and the rest is the same as in Example 1, to obtain an iodine-doped sulfide electrolyte Li6PS5Cl 0.7 I 0.3 .

[0047] Example 4

[0048] In this embodiment, the stoichiometric ratio in step (1) is: Li2S:P2S5:LiCl:LiI=5:1:1.2:0.8, and the rest is the same as in Example 1, to obtain an iodine-doped sulfide electrolyte Li6PS5Cl 0.6 I 0.4 .

[0049] Comparative Example 1

[0050] This comparative example is used to illustrate the interface instability of the sulfide electrolyte without iodine doping to metallic lithium.

[0051] This comparative example relates to a method for preparing a Li6PS5Cl sulfide electrolyte, comprising the following steps:

[0052] (1) In a glove box under argon atmosphere, Li2S, P2S5, and LiCl precursors were weighed and mixed in anhydrous tetrahydrofuran with a stoichiometric ratio of Li2S:P2S5:LiCl=5:1:2, and the mixture was dissolved in anhydrous tetrahydrofuran. The mass fraction of the precursor in the solution was controlled to be 4wt%, and the mixture was stirred for 6h until a uniform beige mixed solution was formed.

[0053] (2) The mixed solution obtained in step (1) was placed on a heating platform and heated to 160° C. for 6 h in an argon atmosphere in a glove box to remove the organic solvent, thereby obtaining a dry mixed precursor.

[0054] (3) The dried mixed precursor obtained in step (2) was placed in a mortar and ground by hand for 10 min into a precursor powder. The powder was transferred to a muffle furnace and heated to 550° C. in an argon atmosphere in a glove box at a heating rate of 2° C. / min and sintered for 6 h to obtain the target sulfide electrolyte.

[0055] (4) In an argon atmosphere in a glove box, the sulfide electrolyte powder obtained in step (3) was placed in a tablet pressing mold with a diameter of 10 mm and pressed into a solid electrolyte sheet at 300 MPa.

[0056] Comparative Example 2

[0057] This comparative example is used to illustrate that the doping amount of iodine element should not exceed a certain limit, otherwise it will cause a sharp drop in ionic conductivity.

[0058] In this comparative example, the stoichiometric ratio in step (1) is: Li2S:P2S5:LiCl:LiI=5:1:1:1, and the rest is the same as in Example 1, to obtain an iodine-doped sulfide electrolyte Li6PS5Cl 0.5 I 0.5 .

[0059] Comparative Example 3

[0060] This comparative example is used to illustrate that under the same iodine doping ratio, non-surface doped (bulk doped) sulfide electrolyte also has interface instability with metallic lithium.

[0061] This comparative example involves Li6PS5Cl 0.7 I 0.3 The preparation method of (bulk phase doping) sulfide electrolyte comprises the following steps:

[0062] (1) In a glove box under argon atmosphere, Li2S, P2S5, LiCl, and LiI precursors were weighed and mixed in anhydrous tetrahydrofuran with a stoichiometric ratio of Li2S:P2S5:LiCl:LiI=5:1:1.4:0.6, and the mixture was dissolved in anhydrous tetrahydrofuran. The mass fraction of the precursor in the solution was controlled to be 4wt%, and the mixture was stirred for 6h to form a uniform mixed solution.

[0063] (2) The mixed solution obtained in step (1) was placed on a heating platform and heated to 160° C. for 6 h in an argon atmosphere in a glove box to remove the organic solvent, thereby obtaining a dry mixed precursor.

[0064] (3) The dried mixed precursor obtained in step (2) was placed in a mortar and ground manually for 10 minutes to form a precursor powder. The powder was transferred to a muffle furnace and heated to 550°C in an argon atmosphere in a glove box at a heating rate of 2°C / min and sintered for 6 hours to obtain a sulfide electrolyte Li6PS5Cl 0.7 I 0.3 .

[0065] (4) In an argon atmosphere in a glove box, the sulfide electrolyte powder obtained in step (3) was placed in a tablet pressing mold with a diameter of 10 mm and pressed into a solid electrolyte sheet at 300 MPa.

[0066] Performance Test:

[0067] 1. XRD test

[0068] The sulfide electrolytes prepared in Example 1 and Comparative Example 1 were subjected to XRD test. They were ground evenly before the test, and the test angle range was between 10° and 70°.

[0069] 2. EIS test

[0070] The sulfide electrolytes prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to impedance tests in a test range of 0.1 Hz to 1 MHz at room temperature.

[0071] 3. Lithium metal stability test

[0072] The sulfide electrolyte sheets prepared in Examples 1-4 and Comparative Examples 1-3 were tested for stability against metallic lithium. Lithium foils were attached to both sides of the electrolyte sheets in an argon atmosphere in a glove box and assembled into metallic lithium symmetric batteries in a test mold. The mold battery was taken out of the glove box and placed on a LAND CT2001A tester for a cycle stability test. The comparison results of the electrolyte ion conductivity and the cycle performance of the assembled metallic symmetric battery in the Examples and Comparative Examples are shown in Table 1.

[0073] Table 1

[0074]

[0075] XRD test results are as follows Figure 1 As shown, the results indicate that the electrolyte prepared by the method of the present invention does not contain other impurities.

[0076] The EIS test results are shown in Table 1 and Figure 2 As shown, the results show that when the iodine doping stoichiometric ratio is x≤0.7, the ionic conductivities of the prepared Examples 1-3 and Comparative Example 1 are in the same order of magnitude, which can meet the requirements of high ionic conductivity of solid electrolytes. When x>0.7, the ionic conductivity of the electrolytes of Example 4 and Comparative Example 2 drops significantly. This result is due to the fact that iodine ions have a larger ionic radius, which causes the sulfide electrolyte to present an ordered lattice structure, thereby hindering the transmission process of lithium ions. When the iodine doping ratio on the electrolyte surface is too high, the transmission process of lithium ions through the electrolyte surface is restricted, resulting in a significant drop in ionic conductivity.

[0077] The stability test results of lithium metal are shown in Table 1 and Figure 3 As shown, it can be seen that the polarization voltage of the metal lithium symmetric battery assembled with the iodine-doped sulfide electrolyte represented by Examples 1-4 and Comparative Example 2 of the present invention is significantly lower than that of the iodine-free sulfide electrolyte represented by Comparative Example 1. At the same time, the stable cycle time of the metal lithium symmetric battery is also better than that of Comparative Example 1. The comparison results of Examples 1-4 show that when the doping stoichiometric ratio of the iodine element increases, the polarization voltage of the metal lithium symmetric battery decreases and the cycle stability improves. This result is due to the fact that a higher surface doping amount of iodine can form a more uniform and stable interface protection layer in situ during the cycle with metal lithium, thereby better inducing the uniform deposition of lithium and inhibiting the occurrence of interface side reactions. In addition, by Figure 3 It can be seen from the cycle data of Example 3 and Comparative Example 3 that, under the same element ratio doping condition, Comparative Example 3 also has the phenomenon of instability to metallic lithium. This result is due to the fact that during the synthesis process of Comparative Example 3, the iodine-containing raw material and the electrolyte raw material are mixed at the same time, resulting in the iodine element in the final synthesized electrolyte being doped in the bulk phase, and it is difficult to form an effective and stable interface protection layer during the contact process with metallic lithium. Therefore, only by controlling the iodine element to form surface doping during the electrolyte synthesis process can the interface stability with metallic lithium be achieved.

[0078] The above examples demonstrate that the interface stability of the sulfide electrolyte to metallic lithium can be improved by surface doping modification with iodine. At the same time, the surface doping content of iodine needs to be controlled within a certain range to ensure that the electrolyte maintains a high ionic conductivity.

[0079] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.

Claims

1. A method for preparing an iodine-doped sulfide electrolyte, characterized in that: The method steps include: (1) Under a protective gas atmosphere, weigh Li2S, LiCl, P2S5, and LiI raw materials according to the stoichiometric ratio, and dissolve Li2S, LiCl, and P2S5 in an organic solvent A and stir to form a precursor solution; (2) heating and drying the precursor solution to remove the organic solvent A to obtain a precursor; (3) placing the precursor in a solution of LiI in an organic solvent B, heating and stirring, to obtain a doped precursor solution; (4) heating and drying the doped precursor solution to remove the organic solvent B to obtain a mixed precursor; (5) grinding the mixed precursor uniformly, placing it in a muffle furnace, calcining it in a protective gas atmosphere, and cooling it after calcination to obtain an iodine-doped sulfide electrolyte; Among them, the chemical formula of the electrolyte is Li6PS5Cl x I 1-x , 0.5 < x < 1; the iodine element is doped on the surface of the argyrodite-type electrolyte Li6PS5Cl 2. The method for preparing an iodine-doped sulfide electrolyte according to claim 1, characterized in that: 0.5<x≤0.7。 3. The method for preparing an iodine-doped sulfide electrolyte according to claim 2, characterized in that: In step (1), the organic solvent A is one or more of anhydrous ethanol, anhydrous acetonitrile and anhydrous tetrahydrofuran; the mass fraction of the precursor solution is 3-6wt%; and the stirring time is 4-6h.

4. The method for preparing an iodine-doped sulfide electrolyte according to claim 2, characterized in that: In step (2), the heating and drying temperature is 160-180°C, and the drying time is 3-5 hours.

5. The method for preparing an iodine-doped sulfide electrolyte according to claim 1, characterized in that: In step (3), the organic solvent B is one or more of anhydrous acetonitrile, anhydrous tetrahydrofuran and anhydrous toluene; the mass fraction of the organic solvent B solution of LiI is 3-6wt%; the heating and stirring temperature is 60-80°C, and the stirring time is 6-8h.

6. The method for preparing an iodine-doped sulfide electrolyte according to claim 1, characterized in that: In step (4), the heating and drying temperature is 160-180°C, and the drying time is 5-8 hours.

7. The method for preparing an iodine-doped sulfide electrolyte according to claim 1, characterized in that: In step (5), the grinding time is 10-30 min; the calcination temperature is 450-600° C., and the calcination time is 4-6 h; during calcination, the heating rate is 1-5° C. / min, and the cooling rate is 1-3 / min.

8. The method for preparing an iodine-doped sulfide electrolyte according to claim 1, characterized in that: The protective gas is nitrogen or an inert gas.

Citation Information

Patent Citations

  • Passivation of sulfide, oxide, and oxysulfide glass electrolyte films for lithium metal batteries

    CN108736069A

  • Lithium ion solid conductor, preparation method thereof and all-solid lithium battery

    CN108899580A